2016
DOI: 10.1080/23723556.2016.1263715
|View full text |Cite
|
Sign up to set email alerts
|

Cancer cell cannibalism and the SASP: Ripples in the murky waters of tumor dormancy

Abstract: Relapse in cancer patients following an apparent cure and a prolonged latency period, known as tumor dormancy, remains an unrelenting clinical crisis. Here, I expand on our recent findings that potentially link cancer cell cannibalism of bone marrow-derived mesenchymal stem/stromal cells (BM-MSCs) to the senescence-associated secretory phenotype (SASP) and tumor dormancy. One mysterious feature of breast cancer is that it can reemerge abruptly many years after apparent eradication of the primary tumor. The asy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
2
3
0
Order By: Relevance
“…In the present study, paired differential expression analysis demonstrated that dormant tumours continue to change under long-term treatment. Some of the identified dormancy-related pathways such as cell cycle arrest and senescence have established roles in metastasis dormancy [38], further supporting the relevance of our clinical model, with the senescence-associated secretory phenotype (SASP) recently suggested to regulate breast cancer dormancy and relapse [39]. As in short-term responsive tumours [16], ECM organization and degradation were significantly upregulated in dormant tumours.…”
Section: Discussionsupporting
confidence: 71%
“…In the present study, paired differential expression analysis demonstrated that dormant tumours continue to change under long-term treatment. Some of the identified dormancy-related pathways such as cell cycle arrest and senescence have established roles in metastasis dormancy [38], further supporting the relevance of our clinical model, with the senescence-associated secretory phenotype (SASP) recently suggested to regulate breast cancer dormancy and relapse [39]. As in short-term responsive tumours [16], ECM organization and degradation were significantly upregulated in dormant tumours.…”
Section: Discussionsupporting
confidence: 71%
“…In the present study, paired differential expression analysis demonstrated that dormant tumours continue to change under long-term treatment. Some of the identified dormancy-related pathways such as cell cycle arrest and senescence have established roles in metastasis dormancy [38] further supporting the relevance of our clinical model, with senescence-associated secretory phenotype (SASP) recently suggested to regulate breast cancer dormancy and relapse [39]. As in short-term responsive tumours [16], ECM organization and degradation were significantly up-regulated in dormant tumours.…”
Section: Discussionsupporting
confidence: 69%
“…Also, Hisamatsu et al reported that the young MSC secretome contains growth differentiation factor 6, which may play an important role in regulating the effects of old-MSC' SASP factors in geriatric diseases [241]. More importantly, MSCs from bone marrow can be cannibalized with other cancerous cells to promote tumor dormancy and SASP factors that contribute to the evolution of tumor recurrence [242].…”
Section: Saspmentioning
confidence: 99%